Koping Stres dan Stres pada Perawat di Rumah Sakit Jiwa “X” - Yulia Dyah Ayu Permatasari; Muhana Sofiati Utami (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
The purpose of this study was to examine the correlation between the dimensions of coping stress and stress among nurses who work on psychiatric units. The hypothesis stated in this study is that there is a correlation between the dimensions of coping stress and stress among nurses who work on psychiatric units at psychiatric hospital “X”. This study used two scale, coping stress scale and stress scale. Subject of this study are psychiatryc units nurses who work in psychiatric hospital “X”. The data from this study was analyzed using correlation product moment technique from Pearson. The result showed that there is no significant correlation between the dimensions of coping stress and stress among nurses who work on pyshiatric room. The analysis result between problem focused coping dimension and stress showed that r = 0.091; p = 0.210 (p > 0.05). Meanwhile, the analysis result between emotional focused coping and stress showed that r = -0.042; p=0.709 (p>0.05). Therefore, the result of this research suggest that there is no significant correlations between the dimensions of coping stress and stress among nurses who work on pyshiatric room.